Ambiguity and the process of knowledge transfer in strategic alliances - Simonin, Bernard L. (Strategic Management Journal, 1999)
This research examines the role played by the ‘causally ambiguous’ nature of knowledge in the process of knowledge transfer between strategic alliance partners. Based on a cross-sectional sample of 147 multinationals and a structural equation methodology, this study empirically investigates the simultaneous effects of knowledge ambiguity and its antecedents—tacitness, asset specificity, prior experience, complexity, partner protectiveness, cultural distance, and organizational distance—on technological knowledge transfer. In contrast to past research that generally assumed a direct relation between these explanatory variables and transfer outcomes, this study’s findings highlight the critical role played by knowledge ambiguity as a full mediator of tacitness, prior experience, complexity, cultural distance, and organizational distance on knowledge transfer. These significant effects are further found to be moderated by the firm’s level of collaborative know-how, its learning capacity, and the duration of the alliance. Copyright © 1999 John Wiley & Sons, Ltd.